Lidar reflective fabric

By using reflectivity-optimized composite materials in LiDAR system, the problem of poor detection effect of dark items in LiDAR system is solved, high reflection of near-IR electromagnetic radiation and low reflection in the visible spectrum is achieved, and detection accuracy is improved .

CN119256127APending Publication Date: 2025-01-03TOYOTA JIDOSHA KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042605.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-02
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing dark items perform poorly in LiDAR systems for obstacle detection and avoidance systems because they absorb electromagnetic radiation in the visible spectrum and do not reflect near IR or LiDAR electromagnetic radiation, resulting in poor detection results.

Method used

A composite material was developed, including black pigments and textile materials, which has a reflectivity of greater than or equal to 12% to near-infrared electromagnetic radiation with wavelengths of 800 nm to 2500 nm and a reflectivity of less than or equal to 10% to visible light from 350 nm to 750 nm. %, and CuO nanoparticles are used to increase the reflectivity of near IR and LiDAR electromagnetic radiation.

Benefits of technology

The ability to effectively detect dark objects in the LiDAR system is realized, and the detection accuracy and reliability of the LiDAR system are improved by the characteristics of low reflectivity and high reflectivity of near IR electromagnetic radiation in the visible spectrum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256127A_ABST
    Figure CN119256127A_ABST
Patent Text Reader

Abstract

A composite material comprising a black pigment and a textile material. The composite material has a reflectance of greater than or equal to 12% for near-infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm, and a reflectance of less than or equal to 10% for visible light having a wavelength of 350 nm to 750 nm. The composite material also has a blackness (My) of 125 to 165.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present specification generally relates to particles that reflect near IR electromagnetic radiation and, more particularly, to copper oxide particles integrated with textile materials that reflect near IR electromagnetic radiation. Background Art

[0002] Light detecting and ranging (LiDAR) systems using pulsed laser electromagnetic radiation with a wavelength of 905 nanometers (nm) or 1050 nm (both of which are in the near infrared ("near IR") portion of the electromagnetic spectrum) have been proposed and tested for use in automatic vehicle obstacle detection and avoidance systems. Although the reflection of near IR electromagnetic radiation facilitates the use of LiDAR, dark (e.g., black) items, such as fabrics, absorb not only visible electromagnetic radiation to form a dark color, but also near IR electromagnetic radiation with wavelengths greater than about 750 nanometers. Therefore, LiDAR-based obstacle detection and avoidance systems may not perform satisfactorily for dark-colored items. Summary of the invention

[0003] Therefore, a need exists for an alternative dark article that absorbs electromagnetic radiation within the visible spectrum but reflects near IR electromagnetic radiation having a wavelength of approximately 905 nm or 1050 nm.

[0004] The first aspect includes a composite material, the composite material comprising: a black pigment; and a textile material, wherein the composite material has a reflectivity greater than or equal to 12% for near infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm, a reflectivity less than or equal to 10% for visible light having a wavelength of 350 nm to 750 nm, and a blackness (M y ) is 125 to 165.

[0005] A second aspect includes the composite material of the first aspect, wherein the black pigment comprises a compound selected from the group consisting of CuO, TiO2, and combinations of two or more thereof.

[0006] The third aspect includes the composite material of any one of the first aspect or the second aspect, wherein the reflectivity of the composite material to visible light with a wavelength of 350 nm to 750 nm is less than or equal to 5%.

[0007] The fourth aspect includes the composite material of any one of the first to third aspects, wherein the reflectivity of the composite material to visible light with a wavelength of 350 nm to 750 nm is less than or equal to 1%.

[0008] The fifth aspect includes the composite material of any one of the first to fourth aspects, wherein the reflectivity of the composite material to near-infrared electromagnetic radiation with a wavelength of 800 nm to 2500 nm is greater than or equal to 15%.

[0009] The sixth aspect includes the composite material of any one of the first to fifth aspects, wherein the reflectivity of the composite material to near-infrared electromagnetic radiation with a wavelength of 800 nm to 2500 nm is greater than or equal to 20%.

[0010] The seventh aspect includes the composite material of any one of the first to sixth aspects, wherein the blackness (M y ) is 130 to 165.

[0011] An eighth aspect includes the composite material of any one of the first to seventh aspects, wherein the black pigment is CuO having an average particle size less than or equal to 5 microns.

[0012] A ninth aspect includes the composite material of any one of aspects 1 to 8, wherein the textile material is a synthetic polymer composition.

[0013] The tenth aspect includes the composite material of any one of the first to ninth aspects, wherein the textile material is selected from polyamide, polyacrylonitrile, polyethylene terephthalate (PET), polybutyrate, polyurethane, nylon, polyester, and combinations of two or more thereof.

[0014] An eleventh aspect includes the composite material of any one of the first to tenth aspects, wherein the composite material has a color with a lightness of L* less than or equal to 40 in the CIELAB color space.

[0015] A twelfth aspect includes the composite material of any one of the first to eleventh aspects, wherein the composite material has a color with a lightness of L* less than or equal to 10 in the CIELAB color space.

[0016] A thirteenth aspect includes the composite material of any one of the first to twelfth aspects, wherein the material has a color with a lightness of L* less than or equal to 1 in the CIELAB color space.

[0017] A fourteenth aspect includes a composite material comprising: CuO; and a textile material, wherein the average particle size of the CuO is less than or equal to 5 microns, and the composite material has a color with a lightness of L* less than or equal to 40 in the CIELAB color space.

[0018] A fifteenth aspect includes the composite material of the fourteenth aspect, wherein the textile material is selected from the group consisting of polyamide, polyacrylonitrile, polyethylene terephthalate (PET), polybutyrate, polyurethane, nylon, polyester, and combinations of two or more thereof.

[0019] A sixteenth aspect includes the composite material of either the fourteenth aspect or the fifteenth aspect, wherein the composite material has a color with a lightness of L* less than or equal to 10 in the CIELAB color space.

[0020] A seventeenth aspect includes the composite material of any one of aspects fourteen to sixteen, wherein the composite material has a reflectivity greater than or equal to 12% to near-infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm.

[0021] An eighteenth aspect includes the composite material of any one of the fourteenth to seventeenth aspects, wherein the reflectivity of the composite material to visible light with a wavelength of 350 nm to 750 nm is less than or equal to 10%.

[0022] The nineteenth aspect includes the composite material of any one of the fourteenth to eighteenth aspects, wherein the blackness (M y ) is 125 to 165.

[0023] The twentieth aspect includes a method for making a black pigment-doped textile material, the method comprising: combining a black pigment with a textile material to form a black pigment-doped textile material, wherein the black pigment-doped textile material has a reflectivity greater than or equal to 12% to near-infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm, a reflectivity less than or equal to 10% to visible light having a wavelength of 350 nm to 750 nm, and a blackness (M) of the black pigment-doped textile material. y ) is 125 to 165.

[0024] The twenty-first aspect includes the method of the twentieth aspect, further comprising extruding the black pigment-doped textile material to produce a composite fiber.

[0025] A twenty-second aspect includes the method of either aspect 20 or aspect 21, wherein extruding comprises heating the black pigment-doped textile material mixture to a softening point of the textile material and drawing the black pigment-doped textile material mixture through a die.

[0026] A twenty-third aspect includes the method of any one of aspects 20 to 22, wherein extruding comprises heating the black pigment-doped textile material mixture to a melting point of the textile material and pulling the black pigment-doped textile material mixture through a die.

[0027] A twenty-fourth aspect includes the method of any one of aspects 20 to 23, wherein extruding comprises drawing the black pigment-doped textile material mixture through a spinneret to produce filaments of the composite fiber.

[0028] A twenty-fifth aspect includes the method of any one of aspects 20 to 24, wherein the black pigment is CuO having an average particle size less than or equal to 5 microns.

[0029] A twenty-sixth aspect includes the method of any of aspects twenty-first through twenty-fifth, wherein the composite fiber has a color with a lightness of L* less than or equal to 40 in the CIELAB color space.

[0030] The twenty-seventh aspect includes a fabric comprising the composite material of any one of the first to thirteenth aspects.

[0031] A twenty-eighth aspect includes the fabric of the twenty-seventh aspect, wherein the black pigment is CuO having an average particle size less than or equal to 5 microns.

[0032] These and additional features provided by the embodiments described herein will be more fully understood in view of the following detailed description taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The embodiments illustrated in the drawings are illustrative and exemplary in nature and are not intended to limit the subject matter defined by the claims. The following detailed description of the illustrative embodiments can be understood when read in conjunction with the following drawings, in which like structures are represented by like reference numerals, wherein:

[0034] Figure 1A The reflectivity of conventional colorants is graphically depicted versus the wavelength of electromagnetic radiation;

[0035] Figure 1B graphically depicts reflectivity of a colorant versus wavelength of electromagnetic radiation according to embodiments disclosed and described herein;

[0036] Figure 2 is a bar graph depicting the blackness of commercially available materials;

[0037] Figure 3 is a graph depicting the reflectivity of commercially available black polyester;

[0038] Figure 4A is a graph depicting reflectivity of CuO nanoparticle-doped polyesters at different levels of reflective LiDAR at wavelengths of electromagnetic radiation ranging from about 250 nm to about 2500 nm;

[0039] Figure 4B is a bar graph depicting reflectivity of CuO nanoparticle-doped polyester with different levels of reflective LiDAR at a wavelength of 910 nm electromagnetic radiation;

[0040] Figure 5A is a graph depicting the reflectivity of polyester doped with 0.5 mass % CuO nanoparticles for reflective LiDAR at wavelengths of electromagnetic radiation from about 250 nm to about 2500 nm at varying levels of carbon black doping; and

[0041] Figure 5Bis a bar graph depicting the reflectivity of polyester doped with 0.5 mass % CuO nanoparticles for reflective LiDAR at different levels of carbon black doping at an electromagnetic radiation wavelength of 910 nm. DETAILED DESCRIPTION

[0042] Embodiments disclosed herein relate to LiDAR reflective dark fabrics. Such LiDAR reflective fabrics can be formed from fibers made of a textile polymer doped with a black pigment. The LiDAR reflective dark fabric has a reflectivity greater than or equal to 12% for near-infrared electromagnetic radiation with a wavelength of 800nm ​​to 2500nm, and a reflectivity less than or equal to 10% for visible light with a wavelength of 350nm to 750nm.

[0043] As used herein, the term "doped" means that a small amount of a substance (e.g., a black pigment; which may be referred to herein as a "dopant") has been added to another material (e.g., a fiber made of a textile polymer). In this context, the term "small amount" refers to up to 5% by weight of the dopant by mass.

[0044] As used herein, the term "near IR electromagnetic radiation" refers to electromagnetic radiation having a wavelength between 800 nm and 2500 nm, inclusive, and "LiDAR" refers to electromagnetic radiation having a wavelength between 905 nm and 1550 nm, inclusive.

[0045] As used herein, the term "visible spectrum" or "visible light" refers to electromagnetic radiation having wavelengths between and including 350 nm and 750 nm.

[0046] As used herein, the term "blackness" or "M y " refers to an experimentally determined property of a material related to its ability to absorb light. The degree of blackness of the paint sample was evaluated by an X-Rite Ci7600 benchtop spectrophotometer (X-Rite, USA) based on a provided reference (i.e., carbon black). It is based on the known formula, see below, where M y Measured at D65 / 10°.

[0047] My=100log(Yn / Y)

[0048] As used herein, the term "reflectivity" refers to a property of a material related to the material's ability to reflect electromagnetic radiation. Reflectivity is quantitatively measured by calibrated analysis of reflectance data collected using a UV-Visible spectrometer.

[0049] As used herein, the term "particle size" refers to the value of at least one dimension of a particle, or when referring to a sample of more than one particle, to the average of at least one dimension of a population of particle samples. Particle size is measured by scanning electron microscopy and transmission electron microscopy.

[0050] As used herein, the term "CIELAB color space" is a color antagonism space based on the nonlinearly compressed CIE space XYZ color space coordinates, which has a brightness dimension L* and color antagonism dimensions a* and b*. The a* axis is perpendicular to the b* axis and forms a chromaticity plane, the L* axis is perpendicular to the chromaticity plane, and the L* axis, in combination with the a* axis and the b* axis, provides a complete description of the color attributes of an object, such as purity, hue, and brightness. Using layman's terms, colorful stimuli (colors) are seen as vivid and intense by the human eye, while less colorful stimuli appear softer and closer to gray. In the absence of "color" at all, the color is a "neutral" gray, and images without color are generally referred to as grayscale images (image ingrayscale) or grayscale images (grayscale image).

[0051] One difficulty in forming a dark (e.g., black) article that reflects LiDAR or near IR electromagnetic radiation is that the visible spectrum of electromagnetic radiation is very close to near IR electromagnetic radiation or LiDAR. Materials that provide dark colors (e.g., black) do not reflect electromagnetic radiation within the visible spectrum of electromagnetic radiation. Such materials also typically do not reflect electromagnetic radiation just outside the visible spectrum of electromagnetic radiation, such as near IR and LiDAR. Carbon black is a material that is commonly used as a dark pigment and does not reflect electromagnetic radiation in the visible spectrum, nor does it reflect near IR or LiDAR electromagnetic radiation. Therefore, a material that does not reflect electromagnetic radiation within the visible spectrum but does reflect near IR or LiDAR electromagnetic radiation needs to have a very sharp increase in reflectivity just outside the visible spectrum of electromagnetic radiation.

[0052] Now refer to Figure 1A , shows the reflectivity of materials commonly used as colorants in a variety of items. Figure 1A The y-axis shows the percentage of ideal reflectivity, and the Figure 1A The x-axis provides the wavelength of electromagnetic radiation. Along the bottom of the graph is shown the reflectivity of a conventional black colorant such as carbon black. Figure 1AAs shown in the figure, the carbon black colorant does not reflect electromagnetic radiation in the visible spectrum (left side of the figure). That is, the reflection of the black colorant is close to zero percent within the visible spectrum of electromagnetic radiation. This shows that the colorant provides a dark, almost pure black color. However, the conventional colorant also reflects about zero percent of electromagnetic radiation outside the visible spectrum (right side of the figure), such as near IR electromagnetic radiation or LiDAR electromagnetic radiation (e.g., greater than about 750 nanometers (nm) to about 1550 nm). Similarly, the reflectivity of white TiO2 used as a conventional white colorant is shown near the top of the figure. As shown in the figure Figure 1A As shown in the right side of the figure, white TiO2 reflects near IR and LiDAR electromagnetic radiation (e.g., greater than about 750nm to 1550nm), wherein the reflection of near IR and LiDAR electromagnetic radiation is greater than 40 percent (at 1550nm) and about 60 percent (at 905nm). However, white TiO2, as the name implies, also reflects electromagnetic radiation within the visible spectrum. Figure 1A As shown, white TiO2 reflects nearly eighty percent of electromagnetic radiation in the visible spectrum. Therefore, neither of these colorants—carbon black or white TiO2—is suitable as a dark particle that also reflects near IR or LiDAR electromagnetic radiation.

[0053] Figure 1B is a graph showing target conditions for particles that do not reflect light in the visible spectrum of electromagnetic radiation but do reflect near IR and LiDAR electromagnetic radiation. Figure 1B In FIG. 1 , the percentage of reflectance is measured along the y-axis, and the wavelength of electromagnetic radiation is provided along the x-axis. The reflectance of a conventional black colorant is shown along the bottom of the graph, which is similar to Figure 1A The reflectivity of conventional black colorants (such as carbon black) shown in FIG. Figure 1B As shown, particles that do not reflect electromagnetic radiation in the visible spectrum but reflect near IR and LiDAR electromagnetic radiation have at least two different reflection regions. The first reflection region is in the visible spectrum of electromagnetic radiation, and the second reflection region is in the visible spectrum of electromagnetic radiation. Figure 1B In this reflective region, particles that do not reflect electromagnetic radiation in the visible spectrum but reflect near IR and LiDAR electromagnetic radiation will behave the same as conventional black colorants (e.g., carbon black, as opposed to white TiO2) by not reflecting electromagnetic radiation in the visible spectrum. Figure 1B As shown, particles that do not reflect electromagnetic radiation in the visible spectrum but do reflect near IR and LiDAR electromagnetic radiation. However, particles that do not reflect electromagnetic radiation in the visible spectrum but do reflect near IR and LiDAR electromagnetic radiation have a second reflective region outside the visible spectrum of electromagnetic radiation.

[0054] The second reflective region covers electromagnetic radiation with wavelengths between 750 nm and 1550 nm, including 750 nm and 1550 nm (this includes near IR and LiDAR electromagnetic radiation). In the second reflective region, particles that do not reflect electromagnetic radiation in the visible spectrum but reflect near IR and LiDAR electromagnetic radiation behave similarly to white TiO2 (as opposed to carbon black) by reflecting a large amount of electromagnetic radiation in the second reflective region. Figure 1B As shown, particles that do not reflect electromagnetic radiation in the visible spectrum but reflect near IR and LiDAR electromagnetic radiation reflect, for example, about 60 percent of LiDAR electromagnetic radiation with a wavelength of 905 nm, and reflect more than 40 percent of LiDAR electromagnetic radiation with a wavelength of 1550 nm. By having a reflectance similar to that of white TiO2 in the second reflective region, the particles can reflect a sufficient amount of near IR and LiDAR electromagnetic radiation so that the particles can be detected by the LiDAR system.

[0055] Figure 1B The difficulty in forming particles that do not reflect electromagnetic radiation in the visible spectrum but reflect near IR and LiDAR electromagnetic radiation is shown. In particular, Figure 1B A sharp increase in reflectance is shown just outside the visible spectrum of electromagnetic radiation. In embodiments, this sharp increase in reflectance occurs at a wavelength of electromagnetic radiation at or about 905 nm, which is a wavelength of electromagnetic radiation typically used in LiDAR systems. Figure 1B As shown, at a wavelength of electromagnetic radiation of about 905 nm, the reflectance increases from about zero percent to nearly sixty percent. Forming particles with such a precise and dramatic increase in reflectance is difficult to achieve, and there is little room for error. For example, if a material reflects too much electromagnetic radiation within the visible spectrum, the appearance of the color will not be pure black, but will have hints of, for example, red or purple. However, if a material does not reflect sufficient amounts of near IR or LiDAR electromagnetic radiation, then the material will not be suitable for detection by a LiDAR system.

[0056] Some materials do not reflect electromagnetic radiation in most of the visible spectrum but reflect near IR and LiDAR electromagnetic radiation; however, these materials have been unable to reproduce the visible appearance of carbon black (ie, having approximately zero percent reflectivity for electromagnetic radiation in the visible spectrum).

[0057] One way to determine this transition from low reflectivity of the visible spectrum of electromagnetic radiation to high reflectivity of near IR and LiDAR electromagnetic radiation is by evaluating the band gap of the material. The band gap generally refers to the energy difference (in electron volts or eV) between the top of the valence band (VB) and the bottom of the conduction band (CB). The VB is the energy band of the electron orbits that electrons can jump out and move to in the CB when excited. The VB is the outermost electron orbit of an atom that an electron can actually occupy. The band gap is the energy required for an electron to move from the VB to the CB, and can represent the conductivity of the material. In the field of optics, the band gap is related to the threshold at which a photon can be absorbed by a material. Therefore, the band gap determines which part of the electromagnetic spectrum a material can absorb. Typically, a material with a large band gap will absorb a larger portion of the electromagnetic spectrum with a short wavelength, while a material with a small band gap will absorb a larger portion of the electromagnetic spectrum with a long wavelength. In other words, a large band gap means that a large amount of energy is required to excite the valence electrons to the CB. In contrast, when the valence band and conduction band overlap (as they do in metals), electrons can easily jump between the two energy bands, which means that the material is highly conductive. However, it has been found that by manipulating the band gap of a material, the type of electromagnetic spectrum absorbed by the material can be controlled. In light of this, materials with band gap energies near the wavelength of electromagnetic radiation detected by LiDAR (about 905nm) or band gaps of about 1.37eV and sharp transitions at the edge of visible light (about 700nm) are promising candidates.

[0058] In an embodiment, the black pigment may include chromium iron oxide and its derivatives. Although chromium iron oxide materials can generally reflect near IR and LiDAR electromagnetic radiation, colorants made from chromium iron oxide materials are often referred to as "cold black bodies" because colorants made from chromium iron oxide or its derivatives have hints of red or blue. Figure 2 is a bar graph showing the blackness of various materials on the y-axis. The blackness is measured by an X-Rite spectrophotometer. Figure 2 On the far left of the graph is carbon black, which is a material commonly used as a black colorant, but carbon black does not reflect near IR or LiDAR electromagnetic radiation. Figure 2 As shown, the blackness of carbon black is about 165. Materials 1 to 7 are chromium iron oxide-containing materials that reflect near IR and LiDAR electromagnetic radiation, but as shown in Figure 2 As can be seen in the Figure 1, these materials have a jetness of about 142 or less. This difference in jetness is significant because materials 1 to 7 have hints of red or blue. Therefore, this considerable jetness gap between the carbon black and materials 1 to 7 indicates that materials 1 to 7 are generally not suitable for use in applications where a true black color is desired, such as in coatings for automotive applications or in black fabrics.

[0059] In an embodiment, the black pigment includes copper (II) oxide or copper oxide (CuO). CuO is a common inorganic compound, which is a black solid material in its natural state. However, not all copper oxides have this black color. That is, another stable copper oxide is cuprous oxide (Cu2O), which is a red solid in its natural state. It is not intended to be bound by any particular theory, and it is believed that the oxidation state of the copper atom is a factor in the color of the compound. CuO is a product of copper mining, and it is a precursor for many other copper-containing products and compounds. CuO has been used as a black pigment in certain applications (e.g., in ceramics, glazes, etc.). However, CuO does not reflect near IR or LiDAR electromagnetic radiation. That is, CuO in its natural state behaves very much like carbon black, because it does not reflect electromagnetic radiation in the visible spectrum, and it does not reflect electromagnetic radiation in the near IR or LiDAR spectrum. Without being bound by any particular theory, CuO has a band gap of 2.0 eV and is not easy to reflect electromagnetic radiation in the near IR or LiDAR spectrum. When CuO is manipulated to have a bandgap more suitable for reflecting electromagnetic radiation in the near IR or LiDAR spectrum, the color of CuO fades to brown-black.

[0060] As mentioned above, articles containing carbon black exhibit very low reflectance (less than 1%) throughout the visible and near IR wavelengths, resulting in high blackness values ​​M y The coatings with commercial CuO selectively show high near-IR reflectivity between 900nm and 1000nm wavelengths of electromagnetic radiation, but CuO shows discernible reflection in visible wavelengths, especially in red hues, resulting in a distinct brownish-hued appearance with a jetness value of M y On the other hand, a "cold black body" exhibits strong reflection at the darker end of the near-IR spectrum at wavelengths of electromagnetic radiation greater than 905 nm, but does not absorb sufficiently in the visible wavelengths, with a blackness value of M y is 125.

[0061] Typically, compounds require a band gap of 1.2 eV to 1.8 eV to absorb (i.e., not reflect) electromagnetic radiation in the visible spectrum and reflect electromagnetic radiation in the near IR and LiDAR spectra. Without manipulation, bulk CuO does not meet these requirements. Bulk CuO has a reported band gap of 2.0 eV and a blackness M of 120 y This band gap is outside the 1.2 eV to 1.8 eV required to reflect electromagnetic radiation in the near IR and LiDAR spectra. Figure 2 The blackness of 120 M y Significantly lower than the blackness of carbon black yThus, in the embodiments disclosed and described herein, the CuO crystallites have a significantly reduced particle size, resulting in a reduced band gap and a lower blackness M of the CuO. y Increase.

[0062] Without being bound by any particular theory, it is believed that the sharp transition in reflectivity (or absorptivity) between 700 nm and 905 nm wavelength electromagnetic radiation can be attributed to the near unity ratio of the (-111) / (111) crystal planes and the approximately Such particles appear to be indistinguishable from carbon black and have the same degree of measured blackness, yet these particles show 1500% better LiDAR detectability than carbon black.

[0063] Methods for making CuO nanoparticles include mechanical methods, such as ball milling, jet milling, or a combination of the two. In an embodiment, the CuO nanoparticles can be formed according to the process disclosed in U.S. Provisional Application No. 63 / 208,783 entitled "Materials with High LiDAR Reflectivity", the entire contents of which are incorporated herein. In short, the method includes combining a precipitant with a solution containing copper nitrate to form a precipitate; drying the filtered precipitate to obtain a dried precipitate; and sintering the dried precipitate to form copper oxide crystallites having an average particle size greater than or equal to 5 nm and less than or equal to 15 nm. The precipitant is selected from sodium hydroxide, sodium carbonate, ammonium carbonate, and a combination of two or more of these.

[0064] In embodiments, CuO crystallites that can be used as a substitute for carbon black and exhibit excellent blackness in the visible spectrum of electromagnetic radiation while also having high reflectivity in near-IR and LiDAR electromagnetic radiation wavelengths can be synthesized by a scalable precipitation-pyrolysis approach—proper selection of the precipitant within a specific concentration range—followed by a well-defined sintering process. Structural and chemical composition studies depict the evolution from precursor to extracted precipitate to final CuO crystallites at different process stages. As described above, two key indicators in the XRD spectrum can be used to direct the experimental conditions to the desired crystal structure and the resulting optical contrast in both the visible and near-IR ranges.

[0065] In an embodiment, the average particle size of the CuO crystallites may be less than or equal to 5.0 μm, such as less than or equal to 4.5 μm, less than or equal to 4.0 μm, less than or equal to 3.5 μm, less than or equal to 3.0 μm, less than or equal to 2.5 μm, less than or equal to 2.0 μm, less than or equal to 1.5 μm, less than or equal to 1.0 μm, less than or equal to 0.5 μm. In such an embodiment, the average particle size of the CuO crystallites may be 0.5 μm to 5.0 μm, such as 1.0 μm to 5.0 μm, 1.5 μm to 5.0 μm, 2.0 μm to 5.0 μm, 2.5 μm to 5.0 μm, 3.0 μm to 5.0 μm, 3.5 μm to 5.0 μm, 4.0 μm to 5.0 μm, 4.5 μm to 5.0 μm, 0.5 μm to 4 .5μm, 1.0μm to 4.5μm, 1.5μm to 4.5μm, 2.0μm to 4.5μm, 2.5μm to 4.5μm, 3.0μm to 4.5μm, 3.5μm to 4.5μm, 4.0μm to 4.5μm, 0.5μm to 4.0μm, 1.0μm to 4.0μm, 1.5μm to 4.0μm, 2.0μm to 4.0μm, 2.5μm to 4.0μm, 3.0μm to 4.0μm, 3.5μm to 4.0μm, 0.5μm to 3.5μm, 1.0μm to 3.5μm, 1.5μm to 3.5μm, 2.0μm to 3.5μm, 2.5μm to 3.5μm, 3.0μm to 3.5μm, 0.5μm to 3.0μm, 1.0μm to 3.0μm, 1.5μm to 3.0μm, 2.0 μm to 3.0μm, 2.5μm to 3.0μm, 0.5μm to 2.5μm, 1.0μm to 2.5μm, 1.5μm to 2.5μm, 2.0μm to 2.5μm, 0. 5 μm to 2.0 μm, 1.0 μm to 2.0 μm, 1.5 μm to 2.0 μm, 0.5 μm to 1.5 μm, 1.0 μm to 1.5 μm, or 0.5 μm to 1.0 μm.

[0066] In one or more embodiments, the average particle size of the CuO crystallites can be less than or equal to 50 nm, less than or equal to 45 nm, less than or equal to 40 nm, less than or equal to 35 nm, less than or equal to 30 nm, less than or equal to 25 nm, less than or equal to 20 nm, less than or equal to 15 nm, or even less than or equal to 10 nm. For example, the average particle size of the CuO crystallites can be 5nm to 15nm, for example, 6nm to 15nm, 7nm to 15nm, 8nm to 15nm, 9nm to 15nm, 10nm to 15nm, 11nm to 15nm, 12nm to 15nm, 13nm to 15nm, 14nm to 15nm, 5nm to 14nm, 6nm to 14nm, 7nm to 14nm, 8nm to 14nm, 9nm to 14nm, 10nm to 14nm, 11nm to 14nm, 12nm to 14nm, 13nm to 14nm, 5nm to 13nm, 6nm to 13nm, 7nm to 13nm, 8nm to 13nm, 9nm to 13nm, 10nm to 13nm, 11nm to 15nm, 12nm to 15nm, 13nm to 15nm, 13nm, 12nm to 13nm, 5nm to 12nm, 6nm to 12nm, 7nm to 12nm, 8nm to 12nm, 9nm to 12nm, 10nm to 12nm, 11nm to 12nm, 5nm to 11nm, 6nm to 11nm, 7nm to 11nm, 8nm to 11nm, 9nm to 11nm, 10nm to 11nm, 5nm to 10nm, 6nm to 10nm, 7nm to 10nm, 8nm to 10nm, 9nm to 10nm, 5nm to 9nm, 6nm to 9nm, 7nm to 9nm, 8nm to 9nm, 5nm to 8nm, 6nm to 8nm, 7nm to 8nm, 5nm to 7nm, 6nm to 7nm, or 5nm to 6nm.

[0067] Without being bound by any particular theory, it is believed that the smaller the average crystal size of the CuO nanoparticles, the lower the band gap of the CuO nanoparticles will be. Therefore, by reducing the bulk CuO particles into CuO nanoparticles according to the embodiments disclosed and described herein, the band gap of the CuO nanoparticles is within a range that will reflect electromagnetic radiation within the near IR and LiDAR spectra. In an embodiment, the band gap of the CuO nanoparticles as measured by X-ray photoelectron spectroscopy (XPS) is 1.2eV to 1.8eV, for example, 1.3eV to 1.8eV, 1.4eV to 1.8eV, 1.5eV to 1.8eV, 1.6eV to 1.8eV, 1.7eV to 1.8eV; is 1.2eV to 1.7eV, for example, 1.3eV to 1.7eV, 1.4eV to 1.7eV, 1.5eV to 1.7eV, 1.6eV to 1.7eV; 1.2eV to 1.6eV, for example, 1.3eV to 1.6eV, 1.4eV to 1.6eV, 1.5eV to 1.6eV; 1.2eV to 1.5eV, for example, 1.3eV to 1.5eV, 1.4eV to 1.5eV; 1.2eV to 1.4eV, for example, 1.3eV to 1.4eV; or 1.2eV to 1.3eV.

[0068] In some embodiments, the black pigment may include a dark pigment disclosed in U.S. Pat. No. 11,118,062, the entire contents of which are incorporated herein by reference. Briefly, the dark pigment includes a core layer formed of a reflective material; a first layer extending on the core layer; a second layer extending on the first layer; and a third layer extending on the second layer. The first layer may be formed of a first absorber material or a first dielectric material and have a thickness of about 5 nm to about 500 nm. The second layer may be formed of a second absorber material different from the first absorber material and have a thickness of about 5 nm to about 50 nm. The third layer may be formed of a third absorber material or a second dielectric material, the third absorber material being different from the second absorber material, and the third layer having a thickness of about 5 nm to about 500 nm. For all incident angles of visible electromagnetic radiation between 0° and 45° and including 0° and 45°, the pigment reflects less than 10% of the incident visible electromagnetic radiation. The pigment reflects greater than 60% of incident near IR electromagnetic radiation having a wavelength between 850 nm and 950 nm, inclusive, for all angles of incidence of the near IR electromagnetic radiation between 0° and 45°, inclusive.

[0069] In an embodiment, the black pigment may be black TiO2 disclosed in U.S. Pre-Grant Publication No. 2021 / 0139713, the entire contents of which are incorporated herein by reference. Black TiO2 has a blackness comparable to that of carbon black. In addition, black TiO2 generally does not show signs of red and brown, and is a good substitute for carbon black. However, standard black TiO2 does not reflect near IR or LiDAR electromagnetic radiation. In addition, compared to carbon black, it is more expensive to prepare black TiO2 because TiO2 naturally has a white color and must be treated, such as by hydrogenation, to form black TiO2. White TiO2 reflects near IR and LiDAR electromagnetic radiation, but when it is treated to become black TiO2, it loses its ability to reflect near IR and LiDAR electromagnetic radiation. Therefore, although black TiO2 is obviously similar to carbon black in terms of its blackness, carbon black is generally preferred over black TiO2 for these reasons and economic reasons. However, white TiO2 can be converted into black TiO2 that does not reflect electromagnetic radiation within the visible spectrum but reflects near IR and LiDAR electromagnetic radiation. In embodiments, black TiO2 has a crystalline titanium dioxide core and an amorphous titanium dioxide shell surrounding the crystalline titanium dioxide core.

[0070] Regardless of which pigment is included in the composite material, in embodiments, the black pigment has a blackness M y 125 to 170, e.g., 130 to 170, 135 to 170, 140 to 170, 145 to 170, 150 to 170, 155 to 170, 160 to 170, 165 to 170, 125 to 165, 130 to 165, 135 to 165, 140 to 165, 145 to 165, 150 to 165, 155 to 165, 160 to 165, 125 to 160, 130 to 160, 135 to 160, 140 to 160, 145 to 160 , 150 to 160, 155 to 160, 125 to 155, 130 to 155, 135 to 155, 140 to 155, 145 to 155, 150 to 155, 125 to 150, 130 to 150, 135 to 150, 140 to 150, 145 to 150, 125 to 145, 130 to 145, 135 to 145, 140 to 145, 125 to 140, 130 to 140, 135 to 140, 125 to 135, 130 to 135, or 125 to 130.

[0071] In an embodiment, the reflectivity of the black pigment in the visible spectrum of electromagnetic radiation (350nm to 750nm) can be less than or equal to 10%, for example, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%, less than or equal to 2%, less than or equal to 1%, or less than or equal to 0.5%.

[0072] In embodiments, the black pigment may have a reflectivity of 10% or greater, e.g., 15% or greater, 20% or greater, 25% or greater, 30% or greater, 35% or greater, 40% or greater, 45% or greater, 50% or greater, 55% or greater, or 60% or greater in the near IR and LiDAR spectrum of electromagnetic radiation (800 nm to 2500 nm).

[0073] The textile material of the composite material is not particularly limited and may refer to any polymer material used to form synthetic fibers. Exemplary textile materials include, but are not limited to, polyamide, polyacrylonitrile, polyethylene terephthalate (PET), polybutyrate, polyurethane, nylon, polyester, and combinations of two or more thereof.

[0074] In an embodiment, the fiber made of the textile polymer can be doped with 0.1% to 5.0% by mass of black pigment, for example, 0.5% to 5.0% by mass of black pigment, 1.0% to 5.0% by mass of black pigment, 1.5% to 5.0% by mass of black pigment, 2.0% to 5.0% by mass of black pigment, 2.5% to 5.0% by mass of black pigment, 3.0% to 5.0% by mass of black pigment, 3.5% to 5.0% by mass of black pigment, 4.0% to 5.0% by mass of black pigment, 4.5% to 5.0% by mass of black pigment, 0.1% to 4.5% by mass of black pigment, 0.5 ...5.0% by mass of black pigment, 2.5% to 5.0% by mass of black pigment, 3.0% to 5.0% by mass of black pigment % to 4.5% by mass of black pigment, 1.0% to 4.5% by mass of black pigment, 1.5% to 4.5% by mass of black pigment, 2.0% to 4.5% by mass of black pigment, 2.5% to 4.5% by mass of black pigment, 3.0% to 4.5% by mass of black pigment, 3.5% to 4.5% by mass of black pigment, 4.0% to 4.5% by mass of black pigment, 0.1% to 4.0% by mass of black pigment, 0.5% to 4.0% by mass of black pigment, 1.0% to 4.0% by mass of black pigment, 1.5% to 4.0% by mass of black pigment, 2.0% to 4.0% by mass of black pigment, 2.5% to 4.0% by mass of black pigment, material, 3.0% to 4.0% by mass of black pigment, 3.5% to 4.0% by mass of black pigment, 0.1% to 3.5% by mass of black pigment, 0.5% to 3.5% by mass of black pigment, 1.0% to 3.5% by mass of black pigment, 1.5% to 3.5% by mass of black pigment, 2.0% to 3.5% by mass of black pigment, 2.5% to 3.5% by mass of black pigment, 3.0% to 3.5% by mass of black pigment, 0.1% to 3.0% by mass of black pigment, 0.5% to 3.0% by mass of black pigment, 1.0% to 3.0% by mass of black pigment, 1.5% to 3.0% by mass of black pigment, 2.0% to 3.0% by mass of black pigment, 2.5% to 3.0% by mass of black pigment, 0.1% to 2.5% by mass of black pigment, 0.5% to 2.5% by mass of black pigment, 1.0% to 2.5% by mass of black pigment, 1.5% to 2.5% by mass of black pigment, 2.0% to 2.5% by mass of black pigment, 0.1% to 2.0% by mass of black pigment, 0.5% to 2.0% by mass of black pigment, 1.0% to 2.0% by mass of black pigment, 1.5% to 2.0% by mass of black pigment, 0.1% to 1.5% by mass of black pigment, 0.5% to 1.5% by mass of black pigment, 1.0% to 1.5% by mass of black pigment, 0.1% to 1.0% by mass of black pigment, 0.5% to 1.0% by mass of black pigment, or 0.1% to 0.5% by mass of black pigment.

[0075] In some embodiments, the composite material can have a color with a lightness L* in the CIELAB color space of less than or equal to 40, less than or equal to 35, less than or equal to 30, less than or equal to 25, less than or equal to 20, less than or equal to 15, less than or equal to 10, less than or equal to 9, less than or equal to 8, less than or equal to 7, less than or equal to 6, less than or equal to 5, less than or equal to 4, less than or equal to 3, less than or equal to 2, or even less than or equal to 1.

[0076] Regardless of the type of pigment included in the composite material, in embodiments, the blackness M of the composite material y 125 to 165, for example, 130 to 165, 135 to 165, 140 to 165, 145 to 165, 150 to 165, 155 to 165, 160 to 165, 125 to 160, 130 to 160, 135 to 160, 140 to 160, 145 to 160, 150 to 160, 155 to 160, 125 to 155, 130 to 155, 135 to 155 , 140 to 155, 145 to 155, 150 to 155, 125 to 150, 130 to 150, 135 to 150, 140 to 150, 145 to 150, 125 to 145, 130 to 145, 135 to 145, 140 to 145, 125 to 140, 130 to 140, 135 to 140, 125 to 135, 130 to 135, or 125 to 130.

[0077] In an embodiment, the reflectivity of the composite material in the visible spectrum of electromagnetic radiation (350nm to 750nm) can be less than or equal to 10%, for example, less than or equal to 9%, less than or equal to 8%, less than or equal to 7%, less than or equal to 6%, less than or equal to 5%, less than or equal to 4%, less than or equal to 3%, less than or equal to 2%, less than or equal to 1%, or less than or equal to 0.5%.

[0078] In embodiments, the composite material may have a reflectivity in the near IR and LiDAR spectrum of electromagnetic radiation (800 nm to 2500 nm) of 12% or greater, e.g., 15% or greater, 20% or greater, 25% or greater, 30% or greater, or 35% or greater. In one or more embodiments, the reflectivity of the composite material in the near IR and LiDAR spectrum of electromagnetic radiation (800nm ​​to 2500nm) can be greater than or equal to 12% and less than or equal to 30%, for example, greater than or equal to 15% and less than or equal to 30%, greater than or equal to 20% and less than or equal to 30%, or greater than or equal to 25% and less than or equal to 30%, greater than or equal to 12% and less than or equal to 25%, greater than or equal to 15% and less than or equal to 25%, greater than or equal to 20% and less than or equal to 25%, greater than or equal to 12% and less than or equal to 20%, greater than or equal to 15% and less than or equal to 20%, or greater than or equal to 12% and less than or equal to 15%.

[0079] It should be understood that in one or more embodiments, the composite material may include a mixture of LiDAR reflective black pigments (such as, for example, CuO and black TiO2) and other commercially available black pigments (such as, for example, carbon black).

[0080] According to some embodiments, a method for making composite fiber is disclosed. Any of the above-mentioned black pigments can be combined with a textile material to form a textile material mixture doped with the black pigment. In an embodiment, combining the black pigment with the textile material can include softening and / or melting the textile material and mixing it into the black pigment. In an embodiment, combining the black pigment with the textile material includes dispersing the black pigment in a solvent and soaking the already formed part of the textile material. Exemplary solvents include water, methanol, ethanol, propanol, isopropanol, pentane, hexane and heptane.

[0081] In embodiments where the textile material is softened and / or melted and then doped with black pigment, the resulting black pigment-doped textile material mixture can then be extruded to produce composite fiber. In embodiments, extrusion can include heating the black pigment-doped textile material mixture to the softening point of the textile material, and drawing the so softened black pigment-doped textile material mixture through a die. In embodiments, extrusion can include heating the black pigment-doped textile material mixture to the melting point of the textile material, and drawing the so melted black pigment-doped textile material mixture through a die. In embodiments, extrusion can include drawing the black pigment-doped textile material mixture through a spinneret, thereby producing filaments of composite fiber.

[0082] In an embodiment, the composite fiber can be used to make a line or yarn that is woven, knitted or otherwise passed through to form a LiDAR reflective black fabric. The LiDAR reflective black fabric can be used in many applications. An exemplary application of the LiDAR reflective black fabric is incorporated into work clothes and uniforms using LiDAR, which are used for road construction, factory work, warehouse operations, or any other work environment with automatic vehicles and other automatic equipment. Another exemplary application of the LiDAR reflective black fabric is incorporated into sportswear, such as running equipment. More examples can include outdoor clothing, such as jackets, coats, parkas, ski pants, and ski suits. When the demand for LiDAR reflective clothing increases as automatic vehicles become more and more common throughout society, other uses can be considered, such as awnings or umbrellas for baby carriages.

[0083] Example

[0084] Embodiments will be further illustrated by the following examples.

[0085] Example 1 - Synthesis

[0086] Analytical grade (AR) copper (II) nitrate Cu(NO3)2, sodium hydroxide (NaOH) and sodium carbonate Na2CO3 and deionized water were used without any further purification from Sigma Aldrich.

[0087] CuO nanoparticles were synthesized by coprecipitation using Na2CO3 or NaOH as precipitants. In a typical synthesis, the required amount of Cu(NO3)2 was dissolved in 300 ml of distilled water. A known concentration of Na2CO3 or NaOH solution was added dropwise to the Cu(NO3)2 solution under vigorous stirring at room temperature. The solution was then stirred for 3 hours and aged overnight before filtering. After overnight aging, the precipitate was filtered and washed with 1000 ml of distilled water. The solid product was then dried at 120°C overnight and sintered from 300°C to 600°C for 3 hours at a heating rate of 5°C / min.

[0088] The crystallographic information of the CuO nanoparticles was investigated using powder X-ray diffraction (XRD, Japan, Rigaku Miniflex 600) with Cu Ka radiation (λ=0.1541 nm). The average crystallite size τ of the prepared particles was estimated from the measured width of their XRD diffraction curves using the Scherrer equation (1).

[0089]

[0090] where k is a dimensionless shape factor that is close to unity, λ represents the wavelength of the X-ray radiation, β is the line broadening at half maximum intensity (FWHM), and θ is the Bragg angle.

[0091] The CuO nanoparticles are then combined with a polymer material and the mixture is heated to at least the softening point of the polymer material and extruded to produce filaments for forming composite fibers.

[0092] The composite fiber thus obtained was woven into a composite fiber fabric sheet. The optical properties of the fabric were determined using a UV / Vis / NIR spectrophotometer (Agilent Cary 7000, USA). The band gap calculation was based on the Kubelka-Munk function F(R) represented by equation (2): ∞ ), which is related to the diffuse reflectance coefficient R ∞ related:

[0093] F(R ∞ )=(1-R ∞ ) 2 / 2R ∞ (2)

[0094] Where R ∞ is the absolute value of the reflection coefficient, and F(R ∞ ) is equivalent to the absorption coefficient. The indirect band gap of the sample is plotted by (F(R ∞ )hv) 0.5 The linear part of the curve is extrapolated to (F(R ∞ )hv) 0.5 = 0 to obtain the indirect band gap energy.

[0095] Fabric blackness degree M y The evaluation was performed by an X-Rite Ci7600 benchtop spectrophotometer (X-Rite, USA) and was directly related to the reference value provided by the instrument according to equation (3):

[0096] M Y =100log(Y n / Y) (3)

[0097] where Y n =100.000 is one of the CIE White Point values ​​for D65 / 10 conditions, and Y is one of the CIE tristimulus values ​​for the sample being tested.

[0098] Comparative Example 1

[0099] The reflectance of a commercially available black polyester (Instamorph Plastic manufactured by Sorfeo Inc.) was measured using a UV-Visible spectrophotometer. Figure 3 is a graph showing reflectivity results at wavelengths of electromagnetic radiation ranging from about 250 nm to about 2500 nm. Figure 3 As shown, the reflectivity at a wavelength of electromagnetic radiation greater than or equal to 910 nm is less than 3%.

[0100] Example 2

[0101] A commercially available white polyester (Instamorph Plastic manufactured by Sorfeo Inc.) was doped with increasing mass percentages of CuO nanoparticles synthesized according to Example 1 above. The doping of the polyester was performed by heating the polyester to above 100°C and then mechanically mixing in the CuO powder. The doped polyester was then cooled back to room temperature. Specifically, seven samples were prepared in which the white polyester was doped with 0.10 mass % CuO nanoparticles, 0.20 mass % CuO nanoparticles, 0.50 mass % CuO nanoparticles, 1.00 mass % CuO nanoparticles, 2.00 mass % CuO nanoparticles, 3.00 mass % CuO nanoparticles, and 5.00 mass % CuO nanoparticles.

[0102] Figure 4A is a graph showing the reflectivity of these samples (as well as an undoped commercially available white polyester) at wavelengths of electromagnetic radiation ranging from about 250 nm to about 2500 nm. Figure 4A As shown, at 0.10 mass % CuO nanoparticle doping, the reflectivity of the doped polyester in the visible electromagnetic radiation spectrum drops to less than 20% (compared to about 40% for the undoped polyester), while the reflectivity of the doped polyester at the electromagnetic radiation wavelength of about 900 nm to about 1600 nm is higher than 40%, and the reflectivity at the electromagnetic radiation wavelength of about 1600 nm to about 2200 nm is close to 20%. In addition, at 0.20 mass % or more CuO nanoparticle doping, the reflectivity of the doped polyester in the visible electromagnetic radiation spectrum drops to less than 10% (to about 5%), while the reflectivity of the doped polyester at the electromagnetic radiation wavelength of about 900 nm to about 1600 nm is about 20% to higher than 40%, and for many samples, the reflectivity at the electromagnetic radiation wavelength of about 1600 nm to about 2200 nm is higher than 10%.

[0103] Figure 4B is a bar graph showing the reflectivity of the sample at an electromagnetic radiation wavelength of 910 nm. Figure 4BAs shown, for the undoped polyester and the polyester doped with 0.10 mass % CuO nanoparticles, the reflectivity is very high, but these samples reflect a large amount of electromagnetic radiation wavelengths in the visible spectrum. However, the polyester samples doped with 0.20 mass % or more reflect more than 15% of electromagnetic radiation with a wavelength of 900 nm, and reflect a small amount of electromagnetic radiation wavelengths in the visible spectrum.

[0104] Example 3

[0105] A commercially available white polyester (Instamorph Plastic manufactured by Sorfeo Inc.) was doped with 0.5 mass % of the CuO nanoparticles synthesized according to Example 1 above. The doping of the polyester was performed by heating the polyester to above 100°C and then mechanically mixing in the CuO powder. The polyester was then cooled back to room temperature. Increasing mass percentages of carbon black (carbon black manufactured by Pearl Ex) were added to the polyester. Specifically, five samples were prepared in which the polyester doped with 0.5 mass % CuO nanoparticles was doped with 0.20 mass % carbon black, doped with 0.40 mass % carbon black, doped with 0.60 mass % carbon black, doped with 0.80 mass % carbon black, and doped with 1.00 mass % carbon black.

[0106] Figure 5A is a graph showing the reflectivity of these samples (as well as a commercially available white polyester doped with 0.5 mass % CuO nanoparticles) at wavelengths of electromagnetic radiation ranging from about 250 nm to about 2500 nm. Figure 5A As shown, all samples have similar reflectivity at electromagnetic radiation wavelengths in the visible spectrum, but when carbon black is added to the polyester, the reflectivity of the polyester at electromagnetic radiation wavelengths from about 900 nm to about 1600 nm decreases, with a significant decrease between 0.20 mass % doping and 0.40 mass % doping. Samples doped with more than 0.40 mass % carbon black have very similar reflectivity at electromagnetic radiation wavelengths from about 900 nm to about 1600 nm.

[0107] Figure 5B is a bar graph showing the reflectivity of the sample at a wavelength of 910 nm electromagnetic radiation. Figure 5B As shown, for polyester doped with 0.5 mass % CuO nanoparticles and without carbon black, the reflectivity is very high. However, when carbon black is added to the polyester, the reflectivity at an electromagnetic radiation wavelength of 910 nm decreases. The reflectivity at an electromagnetic radiation wavelength of 910 nm stabilizes to less than 20% after 0.6 mass % carbon black loading.

[0108] Although specific embodiments have been shown and described herein, it should be understood that various other changes and modifications may be made without departing from the spirit and scope of the claimed subject matter. In addition, although various aspects of the claimed subject matter have been described herein, such aspects need not be used in combination. Therefore, the appended claims are intended to cover all such changes and modifications within the scope of the claimed subject matter.

Claims

1. A composite material comprising: Black pigment; and Textile materials, including The composite material has a reflectivity greater than or equal to 12% to near-infrared electromagnetic radiation with a wavelength of 800 nm to 2500 nm, The composite material has a reflectivity of less than or equal to 10% for visible light with a wavelength of 350 nm to 750 nm, and The blackness (M y ) is 125 to 165.

2. The composite material according to claim 1, wherein the black pigment comprises a compound selected from the group consisting of CuO, TiO2, and combinations of two or more thereof. 3 . The composite material according to claim 1 , wherein the composite material has a reflectivity of less than or equal to 5% to visible light with a wavelength of 350 nm to 750 nm. 4 . The composite material according to claim 1 , wherein the composite material has a reflectivity of less than or equal to 1% to visible light with a wavelength of 350 nm to 750 nm.

5. The composite material of claim 1, wherein the composite material has a reflectivity greater than or equal to 15% to near infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm.

6. The composite material of claim 1, wherein the composite material has a reflectivity greater than or equal to 20% to near infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm.

7. The composite material according to claim 1, wherein the blackness (M y ) is 130 to 165.

8. The composite material of claim 1, wherein the black pigment is CuO having an average particle size less than or equal to 5 microns.

9. The composite material of claim 1, wherein the textile material is a synthetic polymer composition.

10. The composite material of claim 1, wherein the textile material is selected from the group consisting of polyamide, polyacrylonitrile, polyethylene terephthalate (PET), polybutyrate, polyurethane, nylon, polyester, and combinations of two or more thereof.

11. The composite material of claim 1, wherein the composite material has a color with a lightness of L* less than or equal to 40 in the CIELAB color space.

12. The composite material of claim 1, wherein the composite material has a color with a lightness of L* less than or equal to 10 in the CIELAB color space.

13. The composite material of claim 1, wherein the composite material has a color with a lightness of L* less than or equal to 1 in the CIELAB color space.

14. A composite material comprising: CuO; and Textile materials, including The average particle size of CuO is less than or equal to 5 microns, The composite material has a color with a lightness of L* less than or equal to 40 in the CIELAB color space.

15. The composite material of claim 14, wherein the textile material is selected from the group consisting of polyamide, polyacrylonitrile, polyethylene terephthalate (PET), polybutyrate, polyurethane, nylon, polyester, and combinations of two or more thereof.

16. The composite material of claim 14, wherein the composite material has a color with a lightness of L* less than or equal to 10 in the CIELAB color space.

17. The composite material of claim 14, wherein the composite material has a reflectivity greater than or equal to 12% to near infrared electromagnetic radiation having a wavelength of 800 nm to 2500 nm. 18 . The composite material according to claim 14 , wherein the composite material has a reflectivity of less than or equal to 10% to visible light with a wavelength of 350 nm to 750 nm.

19. The composite material according to claim 14, wherein the blackness (M y ) is 125 to 165.

20. A method for producing a black pigment-doped textile material, the method comprising: combining a black pigment with a textile material to form the black pigment-doped textile material, wherein The black pigment-doped textile material has a reflectivity greater than or equal to 12% to near-infrared electromagnetic radiation with a wavelength of 800 nm to 2500 nm, The black pigment-doped textile material has a reflectivity of less than or equal to 10% to visible light with a wavelength of 350 nm to 750 nm, and The blackness (M y ) is 125 to 165.

21. The method of claim 20, further comprising extruding the black pigmented textile material to produce a composite fiber.

22. The method of claim 21, wherein the extruding comprises heating the black pigmented textile material to a softening point of the textile material and drawing the black pigmented textile material through a die.

23. The method of claim 21, wherein the extruding comprises heating the black pigment-doped textile material to a melting point of the textile material and drawing the black pigment-doped textile material through a die.

24. The method of claim 21, wherein the extruding comprises drawing the black pigment-doped textile material through a spinneret to produce filaments of the composite fiber.

25. The method of claim 20, wherein the black pigment is CuO having an average particle size less than or equal to 5 microns.

26. The method of claim 20, wherein the black pigmented textile material has a color with a lightness of L* less than or equal to 40 in the CIELAB color space.

27. A fabric comprising the composite material according to claim 1.

28. The fabric of claim 27, wherein the black pigment is CuO having an average particle size less than or equal to 5 microns.